A Research on Environmental Literacy of Religious Culture and Moral Knowledge Teacher Trainees - (:unkn) unknown (MARMARA UNIV, 2018)
Through this study, of it is aimed to identify the level of environmental literacy of religious culture and moral knowledge teacher trainees and quantitative method is used for the subdivision of attitudes, susceptibility and behaviors towards the environment; qualitative method is used for the subdivision of awareness. For this purpose, a tool of attitude towards the environment, a tool for measuring behavior towards the environment, a tool for measuring sensitivity towards the environment and a tool for measuring the awareness towards the environment were applied to 76 religious culture and moral teacher candidates from different universities which were continuing the pedagogical formation certificate program at Marmara University Ataturk Education Faculty. In the analysis of the data, the t-test and variance analysis techniques were used to analyze the content by composing items from the data obtained from the measurement tool of the awareness towards the environment. As a result of this research, it is identified that the level of environmental literacy of teacher trainees is intermediate.
Keywords: Environmental Problems; Environmental Education; Environmental Literacy; ATTITUDES